Current Advance and Future Prospects of Tissue Engineering Approach to Dentin/Pulp Regenerative Therapy - Ting Gong; Boon Chin Heng; Edward Chin Man Lo; Chengfei Zhang (Stem Cells International)
Recent advances in biomaterial science and tissue engineering technology have greatly spurred the development of regenerative endodontics. This has led to a paradigm shift in endodontic treatment from simply filling the root canal systems with biologically inert materials to restoring the infected dental pulp with functional replacement tissues. Currently, cell transplantation has gained increasing attention as a scientifically valid method for dentin-pulp complex regeneration. This multidisciplinary approach which involves the interplay of three key elements of tissue engineering—stem cells, scaffolds, and signaling molecules—has produced an impressive number of favorable outcomes in preclinical animal studies. Nevertheless, many practical hurdles need to be overcome prior to its application in clinical settings. Apart from the potential health risks of immunological rejection and pathogenic transmission, the lack of a well-established banking system for the isolation and storage of dental-derived stem cells is the most pressing issue that awaits resolution and the properties of supportive scaffold materials vary across different studies and remain inconsistent. This review critically examines the classic triad of tissue engineering utilized in current regenerative endodontics and summarizes the possible techniques developed for dentin/pulp regeneration.